Anterior Decompression and Fusion Versus Laminoplasty for Cervical Myelopathy Caused by Soft Disk Herniation: A Long-term Prospective Multicenter Study. Issue 10 (December 2020) - Koakutsu, Tomoaki; Aizawa, Toshimi; Sasaki, Morichika; Sekiguchi, Akira; Morozumi, Naoki; Ishii, Yushin; Kokubun, Shoichi; Hashimoto, Ko; Kasama, Fumio; Tanaka, Yasuhisa; Sato, Tetsuro; Itoi, Eiji; et al.
Abstract : Study Design: A prospective multicenter study. Objective: The purpose of this study was to determine whether laminoplasty (LP) is comparable for myelopathy caused by cervical disk herniation (CDH). Summary of Background Data: Anterior decompression and fusion (ADF) has conventionally been used for myelopathy caused by CDH with stable outcomes. However, recurrence of myelopathy due to adjacent segment degeneration are its drawbacks. The efficacy of LP without discectomy has been sporadically reported, but no long-term prospective study has been conducted to verify it. Materials and Methods: Patients with cervical myelopathy caused by CDH were studied. The first 30 patients and the next 30 patients were treated with ADF and LP, respectively. The outcomes were compared between the 22 ADF patients and the 20 LP patients who had completed the follow-up examination scheduled 10 years after surgery. Results: There was no statistically significant difference in the postoperative severity or recovery rate of myelopathy between the 2 groups 10 years after surgery. One patient in the ADF group underwent LP for secondary myelopathy due to adjacent segment degeneration 2 years after the surgery. Reoperation was not required for patients in the LP group. Postoperative neck pain was significantly more severe in the LP group than in the ADF group. Conclusions: ADF and LP for cervical myelopathy caused by CDH achieve similarly favorable outcomes. Recurrence of myelopathy caused by adjacent segment degeneration is a disadvantage of ADF while residual neck pain is a disadvantage of LP.